Flexible Electronics: A Bi‐Sheath Fiber Sensor for Giant Tensile and Torsional Displacements (Adv. Funct. Mater. 35/2017). (September 2017) - Wang, Run; Jiang, Nan; Su, Jian; Yin, Qu; Zhang, Yue; Liu, Zhongsheng; Lin, Haibao; Moura, Francisco A.; Yuan, Ningyi; Roth, Siegmar; Rome, Richard S.; Ovalle‐Robles, Raquel; et al.
Abstract : A highly stretchable, resistive strain sensor composed of a bi‐sheath structure is described by Jianning Ding, Linqi Shi, Zunfeng Liu, and co‐workers in article number1702134 . Buckles of a carbon nanotube sheath contact with one another under compression of an underlying buckled elastomer sheath, which is co‐axially coated on a rubber fiber. Stretching separates the buckles, resulting in linear increase of resistance with strain.